Industrial service spillovers across the urban hierarchy and land price gradients - Xian Zheng; Xingtao Chen; Mingzhi Hu (Journal of Urban Management, 2024)
In this study, we investigate how geographic proximity to industrial services provided by cities across the urban hierarchy contributes to differences in land prices of nearby towns. We construct three urban hierarchy tiers for cities in China based on their administrative levels. Using over 78,000 transaction data on the transfer of the land-use rights of industrial land between 2009 and 2019 from the China Land Market Network website, we observe spatial patterns in the spillover effect of industrial services. Land prices tend to decline with great distances from cities providing industrial services. Moreover, the spillover effects of urban service for the higher tiers of the urban hierarchy are large. Our results suggest that policymakers and urban planners should re-evaluate the agglomeration spillover effect because it may not fully consider the position of urban concentrations in the urban hierarchy.